Dukungan Keluarga Dalam Memotivasi Remaja Berprestasi di Sekolah Menengah Atas Negeri 3 Denpasar - Krisna Wiyanti, Ni Ketut Diasari; Tamim, Imron Hadi; Krisna Aditya, I Gst. Ngr Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study is entitled *"Family Support in Motivating Adolescents to Achieve Success at Senior High School 3 Denpasar"* and aims to analyze the form of family support that influences adolescent achievement motivation both in academic and non-academic fields. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through semi-structured interviews, observations, and documentation of high-achieving students and their parents. David McClelland's motivation theory is used as a basis for understanding the dynamics of adolescent motivation based on the need for achievement, affiliation, and power.The results of the study show that family support plays a very important role in shaping adolescent achievement motivation. Forms of support include emotional support in the form of attention, praise, and positive reinforcement; financial support such as financing education and providing learning facilities; and instrumental support through active parental involvement in learning and school activities. These findings indicate that when adolescents feel appreciated and supported by their families, the drive to achieve success increases. In addition, there is also a need to please parents and maintain harmony in family relationships, which further encourages the spirit of achievement.This study also revealed that not all families are able to provide optimal support, due to limited time, understanding, or economic conditions. However, strategies such as effective communication, providing controlled freedom, and collaboration between schools and families have been shown to strengthen adolescent motivation. Therefore, synergy between families and educational institutions is a crucial factor in supporting adolescent success. Keywords: Family support, achievement motivation, adolescents, family, SMA Negeri 3 Denpasar .